Catálogos temáticos: experiência extensionista na área de História - Moura, Denise Aparecida Soares de [UNESP]; Luchetti, Nayara Vignol [UNESP]; Leopaci, Juliana [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work describes an extension project in the area of History. The goal was to organize access to various types of correspondence produced by the colonial councils in Brazil during the 17th and 18th centuries, which were sent to the Overseas Council (the administrative center of the Portuguese Empire) located in Lisbon. Originally in manuscript form, these correspondences were digitized by the Barão do Rio Branco Rescue Project, together with many other types of documents, and were brought to Brazil as 380 CDROMs in around the year 2000, at the time of the commemoration of the 500th anniversary of Brazil’s discovery. History undergraduate students constructed a catalogue locating the correspondence in each of the CD-ROMs.

Este es un relato de experiencia de extensión en el campo de Historia. El objetivo del trabajo ha sido organizar el acceso a una correspondencia producida por las cámaras coloniales del Brasil, entre los siglos XVII y XVIII y enviados al Consejo de Ultramar en Lisboa. Esas correspondencias fueron escaneadas por el Proyecto Rescate Barão de Rio Branco y traídas a Brasil a mediados del año 2000, durante las conmemoraciones de los 500 años del descubrimiento de Brasil, en 380 soportes digitales. Los estudiantes de Historia han creado un catálogo que proporciona la ubicación de estas correspondencias en los soportes digitales.

Este é um relato de experiência extensionista na área da História. O objetivo do trabalho foi organizar o acesso a uma correspondência produzida pelas câmaras coloniais do Brasil, entre os séculos XVII-XVIII e enviados para o Conselho Ultramarino em Lisboa. Estas correspondências foram digitalizadas pelo projeto Resgate Barão do Rio Branco e trazidas para o Brasil por volta do ano 2000, ocasião das comemorações dos 500 anos dos descobrimentos do Brasil, em 380 mídias digitais Estudantes do curso de História  criaram um catálogo que fornece a localização destas correspondências nas mídias.
Thematic catalogues: extension work in the area of history
Catàlogos temáticos: experiência de extensión en el campo de historia
Keywords: Documents; Municipal council; Catalogue; Documentos; Cámaras municipales; Catálogo; Humanas; Cultura; Educação; Documentos; Câmaras municipais; Catálogo